Pengembangan Buku Ajar Pendidikan Kewarganegaraan Insersi Pendidikan Antikorupsi sebagai Penguatan Nilai Integritas Mahasiswa - Karim, Abdul; Rinenggo, Alil; Sholikhah, Ni’matu; Widayati, Sri (Journal of Civic Education, 2024)
The integration of anti-corruption education at the university level can be effectively achieved through its inclusion in civic education. This subject is critical yet has been insufficiently addressed in the textbooks currently in use, which were published by the Directorate General of Learning and Student Affairs in 2016. Lecturers responsible for General Compulsory Courses (MKWU) are required to develop Citizenship Education textbooks that incorporate anti-corruption content. This study aims to assess the feasibility of developing such textbooks and to evaluate their potential in enhancing students' integrity. The research follows a Research and Development (R&D) approach using the ADDIE model, which includes stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection methods involved questionnaires to assess needs and literature reviews to analyze how the textbooks contribute to reinforcing students' integrity. The findings indicated that the media expert assessment scored 86.11%, material experts 92.77%, and student trials 81.625%, all classified as "Very Eligible." The overall average score was 86.835%, confirming the textbook’s suitability. These results demonstrate that the development of a Citizenship Education textbook with an anti-corruption focus effectively supports the cultivation of integrity among students.